2014
DOI: 10.1177/011719681402300408
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction of Sri Lankan and Indian Skilled Migrants in Australia

Abstract: Achieving higher life satisfaction is one of the main reasons for migration. Using cross-sectional survey data, this study explored the life satisfaction of 306 Indian and Sri Lankan skilled migrants employed in Australia. The results indicated that the life satisfaction of the participants was slightly above the Australian normative standard. Achievements in life, standard of living, feeling part of the community, and personal relationships were important domains in participants' lives. There was no relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…This study adds further evidence to previous research on Asian‐born migrants based on HILDA which found health advantages, existence of the healthy immigrant effect and subsequent erosion of it with increasing duration of residence . This study also adds further information to another study using HILDA data which showed differences in physical health, mental health and self‐assessed health between foreign‐born people from English‐speaking and non–English‐speaking countries in comparison with native‐born Australians .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study adds further evidence to previous research on Asian‐born migrants based on HILDA which found health advantages, existence of the healthy immigrant effect and subsequent erosion of it with increasing duration of residence . This study also adds further information to another study using HILDA data which showed differences in physical health, mental health and self‐assessed health between foreign‐born people from English‐speaking and non–English‐speaking countries in comparison with native‐born Australians .…”
Section: Discussionsupporting
confidence: 78%
“…This study found that Asian‐born migrants generally reported a lower decline in functional limitations and life satisfaction compared to the Australian‐born participants over the 5‐ and 10‐year periods. These results added longitudinal findings to a previous cross‐sectional study among Sri Lankan and Indian skilled migrants who also reported higher life satisfaction among self‐selected migrants compared to Australian normative standards . Migrants also face different challenges, with language being one of the most common barriers among older migrants .…”
Section: Discussionsupporting
confidence: 55%
“…Click here to access/download;Manuscript;Manuscript_SWB in India_revised_2.docx Click here to view linked References Thailand, and Algeria); migration is often undertaken as a means to increase wellbeing [26], which may help explain this result. The authors suggest that this work needs to be compared with research conducted in India or Sri Lanka, to determine if these means are consistent with the means in their country of birth.…”
Section: Manuscriptmentioning
confidence: 99%
“…Another body of research in India has adopted a domain-based approach [25] and there is some evidence that domain-based scales may detect associations not found using single item measures [21]. One study [26] used the PWI in an Australian sample of 306 Sri Lankan and Indian first-generation migrant workers. Means for the PWI in this sample were slightly above the mean for Australia, and well above the means found in some other non-western countries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a result of the literature review, we did not find any study investigating the relationship between social support and life satisfaction or self-confidence with social support. When the studies on migrants were examined, it was noted that the issue of social support was separately addressed (Çetin, 2009;Yaşar et al, 2014) and the issue of life satisfaction was addressed separately (Akhan and Batmaz, 2015;Calvo et al, 2017;Gunasekara et al, 2014;Kim, 2000;Şeker and Sirkeci, 2014;Vohra and Adair, 2000). In this context, it was aimed to examine whether the perceived social support of migrants has an impact on life satisfaction and self-confidence levels.…”
Section: Kahramanmaraş Sütçü İmam Universitymentioning
confidence: 99%